Management of Local Skin Reactions Caused by 5-FU 4% Cream for the Treatment of Actinic Keratosis: A Delphi Consensus - Brancaccio, Gabriella; Briatico, Giulia; Apalla, Zoe; Dummer, Reinhard; Eklind, Jan; Seguin, Nicole Basset; Dreno, Brigitte; Fargnoli, Maria Concetta; Guitera, Pascale; Heppt, Markus; Hoeller, Christoph; Jouary, Thomas; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Treatments such as 4% 5-fluorouracil (5-FU) cream have demonstrated strong efficacy in lesion clearance of actinic keratosis; however, local skin reactions (LSR) during treatment remain a significant challenge, potentially affecting patient adherence. Objective: We sought to build consensus on management of LSR associated with 4% 5-FU using the Delphi methodology. Methods: Twenty-eight expert dermatologists participated in a 3-round Delphi process. Experts evaluated LSR management strategies, including emollients, antibiotics, steroids, and treatment discontinuation. Agreement levels were measured using a 7-point Likert scale. Consensus was categorized as high if >80% of votes were within the 5–7 rating range and low when >25% were in the 1–3 rating range, with <25% of the votes in the 6–7 rating range. Other combinations of votes were considered as having moderate agreement. Results: High agreement was achieved for the following statements: the approved daily schedule (once daily for 4 weeks) is the most appropriate (92.9%); mild LSR generally do not require intervention and do not impact treatment adherence (96.4%); severe LSR may benefit from temporary treatment interruption and emollient use, ensuring adherence without compromising efficacy (92.9%). The use of emollients (in parallel with the treatment with 5-FU) was considered not needed by most (moderate consensus, 64.3%). Experts emphasized the importance of clear communication about LSR during baseline consultation to enhance patient compliance. Conclusion: This consensus provides practical guidance for managing LSR induced by 4% 5-FU, ensuring high adherence and optimizing treatment outcomes. Further research is needed to validate these findings and explore alternative management approaches.
CRIS-Team Scopus Importer:2025-05-23
Keywords: 5-fluorouracil; Actinic keratosis; Local skin reactions